The sleep revolution : transforming your life, one night at a time - Huffington, Arianna Stassinopoulos, 1950- (Harmony Books, 2016)
"In her new book, Arianna Huffington, the co-founder and editor-in-chief of The Huffington Post, and the author of the #1 New York Times bestseller Thrive delves into the sleep revolution that is happening all across the world-- a revolution that can transform our lives. Sleep, she writes, is one of humanity's great unifiers, binding us to each other, to our ancestors, to our past, and to the future. Yet we find ourselves in the middle of a crisis of sleep deprivation, with devastating effects on our health, our happiness, our job performance, and our relationships. Only by renewing our relationship with sleep, she writes, can we take control of our lives, live more fully, be more engaged with ourselves and with the world, and more able to meet the inevitable challenges we all face. In Thrive, Arianna Huffington introduced her readers to the importance of sleep as a part of redefining success through well-being, wisdom, wonder, and giving. The topic struck such a powerful chord, resonating so intensely with her readers and her audiences around the world that she realized the power of sleep needed a full exploration. The result is a sweeping, scientifically rigorous, and deeply personal look at sleep, from its history though the ages and the current crisis of sleep deprivation, to the mysteries of dreams and the golden age of sleep science that is revealing all the ways sleep plays a vital role in our health, happiness, well-being, and productivity. In The Sleep Revolution, Arianna identifies the many ways our cultural dismissal of sleep as time wasted undermines our health and our decision-making, and ravages our relationships, our work lives, and even our sex lives. She takes on sleep from every angle, exploring the latest science on sleep, the manipulative and dangerous sleeping pill industry, and all the ways our addiction to technology disrupts our sleep. She also presents scientific recommendations and expert tips on how we can all achieve better and more restorative sleep, and learn how to make the power of sleep work for us. Most important, by highlighting the many areas where sleep's benefits are being rediscovered--from the world of sports and technology to college campuses, the hotel industry, and even workplaces around the world--she points the way forward to amazing innovations, reforms, and inventions rooted in our new love affair with sleep. In today's 24/7 fast-paced, always-connected, perpetually harried, and sleep-deprived world, the hunger for sleep is only getting stronger. The Sleep Revolution both sounds the alarm on the worldwide sleep crisis, and offers a road map for how we can take back our sleep and transform our lives and our world"--